2008
DOI: 10.1007/s10535-008-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of copper on reactive oxygen species, lipid peroxidation and antioxidants in Lemna minor

Abstract: Lemna minor L. treated with 20, 50, or 100 μM CuSO 4 accumulated Cu and reactive oxygen species (hydrogen peroxide and superoxide radical) in frond and root cells. The time-course analysis of lipid peroxidation showed high increment in malondialdehyde production only after 12 and 48 h of Cu treatment. Guaiacol peroxidase and superoxide dismutase activities decreased after 48 h while glutathione reductase activity enhanced 48 h after Cu-treatment. Ascorbate and glutathione contents increased with the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…On the other hand, treatment with Hg as well as Cd or Cr, increased ascorbic acid level in L. minor. Enhanced levels of ascorbic acid were also reported in L. minor treated with Cu [24], Zn treated Brassica juncea [46] and Hg exposed Bacopa monnieri [29]. In addition, Sinha et al [15] reported that in Cr treated Pistia stratioites, ascorbic acid concentration increased after 48 and 96 h of treatment but decreased after 144 h of exposure.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…On the other hand, treatment with Hg as well as Cd or Cr, increased ascorbic acid level in L. minor. Enhanced levels of ascorbic acid were also reported in L. minor treated with Cu [24], Zn treated Brassica juncea [46] and Hg exposed Bacopa monnieri [29]. In addition, Sinha et al [15] reported that in Cr treated Pistia stratioites, ascorbic acid concentration increased after 48 and 96 h of treatment but decreased after 144 h of exposure.…”
Section: Discussionmentioning
confidence: 79%
“…There are few studies of oxidative stress in duckweeds caused by heavy metal treatments in periods of 24 h or less [24][25][26]. These studies suggested that increased concentrations of Cu and Cd affected physiological and biochemical processes in L. minor by inducing oxidative stress, enhancing lipid peroxidation and regulating the antioxidative system.…”
Section: Discussionmentioning
confidence: 99%
“…Cu ion stress has been found to increase titers of antioxidants (ASA, proline and total phenols) (Panda 2008). In the present investigation significant production of ASA, total phenols and proline in Cu-stressed seedlings and their slight enhancement upon EBL and Put application alone or in combinations revealed high antioxidant activities of radish seedlings under Cu ion stress and normal conditions (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports on Cu 2+ stress have concentrated mainly on growth inhibition (including root inhibition), Cu accumulation in the organism, and antioxidant enzymes of plant leaves (Maksymiec and Krupa, 2007;Khatun et al, 2008;Wei et al, 2008), but there are far fewer on the responses of root antioxidant enzymes to copper stress (Panda, 2008;Kováèik et al, 2009;Madejón et al, 2009). L. perenne and F. arundinacea are common turfgrasses in north China.…”
Section: Introductionmentioning
confidence: 99%